Aplikasi Tinder Sebagai Media Mencari Pasangan Dalam Membangun Interaksi Pada Kalangan Remaja Di Kota Makassar - Yuni Sarah; Andi Agustang; M. Ridwan Said Ahmad (Universitas Palangka Raya, 2024)
This research aims to find out 1) how the Tinder application as a medium for finding partners builds interaction among teenagers in the city of Makassar.2) the reason someone uses the Tinder application. This type of research is qualitative research and a descriptive approach. The number of informants in this study was 3 Tinder users who had found a partner on the application and 5 users who had not found a partner using the Snowball sampling technique. Data collection techniques are observation, interviews and documentation. Checking the validity of the data is carried out by member check. Data analysis, namely data reduction, data presentation, and drawing conclusions. The results of this research show that: 1) Choosing to use Tinder is a method used to build interaction among teenagers by using the term match as the first step in interaction and continuing with communication, the basic beginning of interaction, namely a) Social contact, and b ) communication. 2) The reason for using Tinder is because you want to find a partner, add new relationships, find new friends and build closer interactions. Apart from that, there are reasons why someone uses Tinder, namely: a) Psychological factors, b) Factors looking for new friends, and c) Factors self-disclosure.